2016
DOI: 10.3847/0067-0049/223/2/21
|View full text |Cite
|
Sign up to set email alerts
|

The Ubv Color Evolution of Classical Novae. Ii. Color–magnitude Diagram

Abstract: We have examined the outburst tracks of 40 novae in the color-magnitude diagram (intrinsic B − V color versus absolute V magnitude). After reaching the optical maximum, each nova generally evolves toward blue from the upper-right to the lower-left and then turns back toward the right. The 40 tracks are categorized into one of six templates: very fast nova V1500 Cyg; fast novae V1668 Cyg, V1974 Cyg, and LV Vul; moderately fast nova FH Ser; and very slow nova PU Vul. These templates are located from the left (bl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(90 citation statements)
references
References 183 publications
8
80
2
Order By: Relevance
“…The early pulse (oscillation) in the V light curve makes a loop in the color-magnitude diagram. This kind of loops were also seen in multiple-peak novae like V723 Cas and V5558 Sgr as discussed by Hachisu & Kato (2016b). We list our results in Table 1. 7.6.…”
Section: V705 Cas 1993supporting
confidence: 71%
See 3 more Smart Citations
“…The early pulse (oscillation) in the V light curve makes a loop in the color-magnitude diagram. This kind of loops were also seen in multiple-peak novae like V723 Cas and V5558 Sgr as discussed by Hachisu & Kato (2016b). We list our results in Table 1. 7.6.…”
Section: V705 Cas 1993supporting
confidence: 71%
“…Template nova tracks in the time-stretched color-magnitude diagram Hachisu & Kato (2016b) proposed six template tracks of novae with well-determined distance modulus in the V band (m − M ) V and color excess E(B − V ). They dubbed them the V1500 Cyg, V1668 Cyg, V1974 Cyg, LV Vul, FH Ser, and PU Vul tracks as shown in Figure 6 Hachisu & Kato (2016b). They categorized 40 novae into one of these six subgroups, depending on their similarity in the (…”
Section: V1974 Cyg 1992mentioning
confidence: 99%
See 2 more Smart Citations
“…The authors note, however, that the possibility of a face-on subgiant companion remains because U Sco is an eclipsing binary and its edge-on disk may not be bright. Hachisu & Kato (2016b) classified 40 classical novae into six classes according to their evolutionary path in the colormagnitude diagram and found that the different paths correspond to differences in the nova speed class and thus the envelope mass. These authors also displayed the color-magnitude evolution during the 2014 outburst of M31N 2008-12a and found that its characteristic properties are similar to those of U Sco and CI Aql, which are both recurrent novae with a subgiant companion, but different from RS Oph which has a red giant companion (see their Figures 72(c), (d), and 76(b)).…”
Section: Absorption By Surrounding Neutral Hydrogenmentioning
confidence: 99%